Produksi Functionally Graded Material (FGM) dari Hydroxyapatite-Serat Sutra untuk Aplikasi di Bidang Biomaterial dengan Teknik Pulse Electric Current Sintering - Tjokorda Gde Tirta Nindhia (Institute of Research and Community Outreach, Petra Christian University, 2006)
This research is intended to produce functionally graded material (FGM) of Hydroxyapatite (Hap)-silk fibroin by pulse electric current sintering in facing the need in biomaterial application. The sample is created with 4 layers with the thickness for each layer is 0,625 mm, so that the total samples thickness become 2.5mm, with diameter 15 mm. The carbon die is used to compact the sample. The composition of lower layer is 100% silk fibroin, after that 90% silk fibroin +10% Hap, third layer was 80% silk fibroin + 20%Hap, and 70% silk fibroin +30% Hap for the upper layer. The properties of the FGM product was characterized by optical microscope and scanning electron microscope (SEM), three point bend with single-edge beam fracture toughness test (KIC). The grade of the FGM material is proven by using electron probe micro analyzer (EPMA). The value of fracture toughness is 0.45 MPa.m1/2. The sample still can support the load after maximum load is reached. Optical micrograph and SEM, and result from EPMA indicate that the Hap-silk fibroin FGM can be produce perfectly by using the method that is introduced in this research. Abstract in Bahasa Indonesia : Penelitian ini bertujuan memproduksi functionally graded material (FGM) dari hydroxyapatite (Hap)-serat sutra, melalui teknik pulse electric current sintering untuk memenuhi tantangan kebutuhan akan bahan jenis ini untuk digunakan dibidang biomaterial. Benda uji terdiri dari 4 lapis dengan ketebalan sama untuk tiap lapisnya sehingga tebal total menjadi 2.5 mm dengan diameter 15 mm. Komposisi lapisan paling bawah adalah 100% serat sutra, setelah itu 90% serat sutra + 10% Hap. Lapisan ketiga dengan komposisi 80% serat sutra + 20% Hap, dan 70% serat sutra + 30% Hap untuk lapisan paling atas. Perilaku produk FGM ini dikarakterisasikan dengan mikroskop optik, mikroskop electron, uji ketangguhan retak three point bend with single-edge. Gradasi (grade) dari FGM dibuktikan dengan electron probe micro analyzer (EPMA). Ketangguhan retak produk ini adalah 0.45 MPa.m1/2. Benda uji masih dapat menahan beban setelah beban maksimun tercapai. Hasil pengamatan dengan optikal mikroskop, elektron mikroskop, dan EPMA menunjukkan HAP-serat sutra FGM dapat dibuat dengan menggunakan cara yang dikembangkan dalam penelitian ini. Kata kunci: Hydroxyapatite, sutra, functionally graded material (FGM), pulse electric current sintering